Recent Existing Condition on Shrimp Culture at Jepara Coast, Central Java - Tita Elfitasari (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2006)
The shrimp culture is collapsing at Jepara coast. Several internal and external reasons have caused this and are needed to be handled seriously. An alternative solution should be conducted and applied without delay. Recent Existing condition of the shrimp culture at Jepara Coast is experiencing a tremendous decline in the last five years. There are four category of internal factors determinant which shows this decline: the development of shrimp culture production, the development of shrimp culture available cultivation area, shrimp culture number of units, and the development of the farmers’ internal revenue. The degradation of the shrimp culture at Jepara coast is mainly caused by environmental and managerial reasons. The environment is no longer supporting the shrimp culture at Jepara coast and to overcome this, a relocation or re-zonation should be applied. As alternative solution, to regain the Jepara region’s aquaculture potencies, a new species can be introduced and applied. In order to develop new species and to sustain its productivity, the new species should have some characteristics as follows: easy to culture, invulnerable to disease, high market demand, high market price, short cultivation period, low production cost, and able to adapt with unfortunate water quality. Key words : Shrimp culture condition, Jepara coast